ZnO-based Gas Microsensors Sensitive to CO at Room Temperature by Photoactivation. (2016) - Vallejos, S.; Gràcia, I.; Figueras, E.; Pizurova, N.; Hubálek, J.; Cané, C.
Abstract: Gas microsensors based on ZnO structures grown via aerosol-assisted chemical vapor deposition are fabricated. The photoactivated and thermoactivated gas sensing properties of these systems toward CO are presented. Results demonstrate photoactivated responses at room temperature with improved characteristics, which include 35% higher response and 7% faster response times, compared to the thermoactivated response of the sensors at 250 °C. This characteristic becomes significantly advantageous as it allows for the sensor to operate without integrated heaters minimizing the power consumption of the system.